Menopausal hormone therapy and lung cancer-specific mortality following diagnosis: the California Teachers Study. - Jessica Clague; Peggy Reynolds; Katherine D Henderson; Jane Sullivan-Halley; Huiyan Ma; James V Lacey; Shine Chang; George L Delclos; Xianglin L Du; Michele R Forman; Leslie Bernstein (PLoS ONE)
Previous results from research on menopausal hormone therapy (MHT) and lung cancer survival have been mixed and most have not studied women who used estrogen therapy (ET) exclusively. We examined the associations between MHT use reported at baseline and lung cancer-specific mortality in the prospective California Teachers Study cohort. Among 727 postmenopausal women diagnosed with lung cancer from 1995 through 2007, 441 women died before January 1, 2008. Hazard Ratios (HR) and 95% Confidence Intervals (CI) for lung-cancer-specific mortality were obtained by fitting multivariable Cox proportional hazards regression models using age in days as the timescale. Among women who used ET exclusively, decreases in lung cancer mortality were observed (HR, 0.69; 95% CI, 0.52-0.93). No association was observed for estrogen plus progestin therapy use. Among former users, shorter duration (<5 years) of exclusive ET use was associated with a decreased risk of lung cancer mortality (HR, 0.56; 95% CI, 0.35-0.89), whereas among recent users, longer duration (>15 years) was associated with a decreased risk (HR, 0.60; 95% CI, 0.38-0.95). Smoking status modified the associations with deceases in lung cancer mortality observed only among current smokers. Exclusive ET use was associated with decreased lung cancer mortality.